Candidiases - Barbedo, Leonardo S.; Sgarbi, Diana B.G. (Brazilian Journal of Sexually Transmitted Diseases, 2010)
The candidiasis or candidosis is a secondary or primary opportunistic mycosis, endogenous or exogenous, recognized as a sexually transmitted disease (STD), caused by yeasts of the genus Candida. The lesions can vary from superficial to deep; moderate, acute or chronic; involving several sites such as mouth, throat, tongue, skin, scalp, genitals, fingers, nails and sometimes internal organs. Species of this genus reside as commensals taking part of normal microbiota of the gastrointestinal tract of 80% of healthy individuals. The candidiasis epidemiology depends on the host predisposition (immunosuppression), parasitic load and fungal virulence, so when these three factors are present, the species of the genus Candida become aggressive, therefore pathogenic. From the nearly 200 species, approximately 10% are considered etiological agents, the main of clinical interest are C. albicans, C. parapsilosis, C. tropicalis, C. glabrata, C. krusei, C. guilliermondii and C. lusitaniae, but cases of emerging species how C. dubliniensis, C. kefyr, C. rugosa, C. famata, C. utilis, C. lipolytica, C. norvegensis, C. inconspicua, C. viswanathii, among others, are being reported due to the high frequency that colonize and infect the human host. The laboratory diagnosis of candidiasis is mainly based on the presence of blastoconidia on direct examination and observation of the culture yeast of cream colored and doughy aspect on Sabouraud agar. The clinical manifestations can be divided into mucocutaneous, systemic and allergic. The lesions are moist and covered with a whitish pseudomembrane which, when removed, shows an erythematous background, while in mucous and; erythematous satellite lesions with aspect scaly, while cutaneous. Remove the predisposing factors and the restoration of the immunity, combined with azole and polyene, are the main treatments for candidiasis.